Global functional variation in alpine vegetation. (6th April 2021) - Testolin, Riccardo; Carmona, Carlos Pérez; Attorre, Fabio; Borchardt, Peter; Bruelheide, Helge; Dolezal, Jiri; Finckh, Manfred; Haider, Sylvia; Hemp, Andreas; Jandt, Ute; Korolyuk, Andrei Yu; Lenoir, Jonathan; et al.
Abstract: Questions: What are the functional trade‐offs of vascular plant species in global alpine ecosystems? How is functional variation related to vegetation zones, climatic groups and biogeographic realms? What is the relative contribution of macroclimate and evolutionary history in shaping the functional variation of alpine plant communities? Location: Global. Methods: We compiled a data set of alpine vegetation with 5, 532 geo‐referenced plots, 1, 933 species and six plant functional traits. We used principal component analysis to quantify functional trade‐offs among species and trait probability density to assess the functional dissimilarity of alpine vegetation in different vegetation zones, climatic groups and biogeographic realms. We used multiple regression on distance matrices to model community functional dissimilarity against environmental and phylogenetic dissimilarity, controlling for geographic distance. Results: The first two PCA axes explained 66% of the species' functional variation and were related to the leaf and stem economic spectra, respectively. Trait probability density was largely independent of vegetation zone and macroclimate but differed across biogeographic realms. The same pattern emerged for both species pool and community levels. The effects of environmental and phylogenetic dissimilarities on community functional dissimilarity had similar magnitude, while the effect of geographic distance was negligible. Conclusions: Plant species in alpine areas reflect the global variation of plant function, but with a predominant role of resource use strategies. Current macroclimate exerts a limited effect on alpine vegetation, mostly acting at the community level in combination with evolutionary history. Global alpine vegetation is functionally unrelated to the vegetation zones in which it is embedded, exhibiting strong functional convergence across regions. Abstract : Plant species in alpine areas reflect the global variation of plant function, but with a predominant role of resource‐use strategies. Current macroclimate exerts a limited effect on alpine vegetation, mostly acting at the community level in combination with evolutionary history. Global alpine vegetation is functionally unrelated to the vegetation zones in which it is embedded, exhibiting strong functional convergence across regions.